ARSITEKTUR NEO VERNAKULAR PENDEKATAN PADA TOURISM CENTER DI KAWASAN WISATA LEMBAH HARAU KABUPATEN LIMA PULUH KOTA - Amirudin Daefi Maulanda; Rita Laksmitasari Rahayu (Universitas Indraprasta PGRI, 2022)
West Sumatra is one of the tourist destinations in Indonesia, including Lima Puluih Kota Regency. Lima Puluh Kota Regency has a diversity of tourism, nature tourism, cultural and historical tourism. Lima Puluh Kota Regency is also a mainstay tourist destination for West Sumatra Province. Lima Puluh Kota District needs to have a tourist destination management center, so a tourist information center design is needed. The tourism information and promotion center (Tourism Center) prioritizes regional aspects as the surrounding environment. The Neo Vernacular concept is suitable to be used as a design concept for this Tourism Center. The image of the gonjong and the relief of the Harau Valley is a new form of mass configuration in this area. The facilities are provided in accordance with the design objectives, which are to accommodate the arts, economics, and cultural activities of the community so as to increase the tourism quality of the Lima Puluh Kota Regency. To strengthen the appearance of the building, several motifs are used, such as kuciang lalok, siriah gading. There are several buildings in one area, such as the main building, homestay building, culinary building, MEP building, service support building. This area is also equipped with an outdoor area.